Digital Taxation for Social Justice: Bridging Equity, Inclusion, and Sustainable Development (Universitas Terbuka, 2025)
Raising revenue with digital methods gives government the chance to shape society by improving inclusion and equity, not only fiscal matters. This study investigates ways digital tax systems work to ensure fairness, openness and equal availability of government aid, considering their effect on underrepresented groups. To do this, the study mixes reviewing medical literature, studying case studies and looking at policy frameworks used in both developed and developing nations. The study concludes that while digital tax systems improve compliance, reduce costs and create more openness, they also lead to problems with digital education, limited infrastructure and leave some groups out of the process. The findings suggest that making good use of proper tax design, public-private alliances and user-driven practices can unite, rather than separate, people from different socioeconomic groups. This paper clarifies how digital governance, tax policies and social inclusion link to sustainable development priorities.